2016
DOI: 10.22453/lsj-017.1.025035
|View full text |Cite
|
Sign up to set email alerts
|

Activités biologiques des extraits aqueux de Pergularia tomentosa L. (Asclepiadaceae)

Abstract: La présente étude porte sur la recherche de l'activité allélopathique de l'extrait aqueux obtenu par reflux de Pergularia tomentosa Ait. (Asclepiadaceae) récoltée dans le Sahara septentrional Est algérien, via l'examen de ses effets sur la germination des graines d'orge Hordeum vulgare L. L'étude réalisée permet de mettre en évidence l'effet inhibiteur sur la germination des graines d'orge traitées. Les extraits aqueux purs et dilués à 50% présentent une capacité inhibitrice exceptionnelle de l'ordre de 100%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Previous studies reported the presence of the ghalakinoside, calactin, uzarigenin, and pergularoside within the roots and desglucouzarin, coroglaucigenin, and uzarigenin together with α-sitosterol glycoside in the leaves (Alsaid et al, 1988;Gohar et al, 2000). According to numerous reports, P. tomentosa leaves are a rich source of flavonoids and cardenolides it can be a good source of natural antioxidant, antibacterial, cytotoxic, and allelopathic compounds (Cherif et al, 2016;Hosseini Kahnouj et al 2017;Lahmar et al, 2017). Despite P. tomentosa has several traditional uses and various biological effects, very little information is available concerning their effects on the arthropod fauna and only few studies refer to the insecticidal activities of this plant (Acheuk and Doumandji-Mitiche 2013;Paul et al, 2011).…”
Section: Evaluation Of Cytotoxic Effects Of Methanolic Extract Of Permentioning
confidence: 99%
“…Previous studies reported the presence of the ghalakinoside, calactin, uzarigenin, and pergularoside within the roots and desglucouzarin, coroglaucigenin, and uzarigenin together with α-sitosterol glycoside in the leaves (Alsaid et al, 1988;Gohar et al, 2000). According to numerous reports, P. tomentosa leaves are a rich source of flavonoids and cardenolides it can be a good source of natural antioxidant, antibacterial, cytotoxic, and allelopathic compounds (Cherif et al, 2016;Hosseini Kahnouj et al 2017;Lahmar et al, 2017). Despite P. tomentosa has several traditional uses and various biological effects, very little information is available concerning their effects on the arthropod fauna and only few studies refer to the insecticidal activities of this plant (Acheuk and Doumandji-Mitiche 2013;Paul et al, 2011).…”
Section: Evaluation Of Cytotoxic Effects Of Methanolic Extract Of Permentioning
confidence: 99%
“…A seed is germinated when there is the opening of the seed and the emergence of a 3 mm stem. [25] According to Côme, the germination rate (Gr) corresponds to the percentage of germinated seeds compared to the total seed sown, it is estimated by the following formula: [26][27] Gr = (Ng / Ns) × 100 Ng: Number of seeds sprouted. Ns: Number of seeds sown.…”
Section: Germination Rate Of the Seeds Of Lepidium Sativummentioning
confidence: 99%
“…It allows a precise vision of the germination evolution of a seed lot placed under specific conditions. [26][27] Germination inhibition rate (GI%) The ability of an extract or substance to inhibit seed germination is expressed by the following relationship: [24] GI% = (PG control -PG test / PG control) × 100 PG control: Germination percentage of the control lot PG test: Germination percentage of the lot treated by extracts Vigor of seedling Lepidium sativum After determination of germination for seven days for each seed lot, a measure of the length of the radical is performed. This value is expressed as an average of extension of rootlets and the results are noted in mm.…”
Section: Kinetics Of Germinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Selon la FAO et International Water Management Institute (2018) chaque année 4,6 millions de tonnes de pesticides chimiques sont pulvérisés dans l'environnement dans le monde et, pays en développement représentent 25% de l'utilisation mondiale des pesticides dans l'agriculture. Cette situation serait à l'origine de la perturbation de l'équilibre écologique de l'écosystème, de la dégradation et de la destruction de la santé, de la biodiversité et de l'environnement (Chérif et al, 2016). Malgré cette forte sollicitation, les producteurs font toujours face à des bio-agresseurs.…”
Section: Introductionunclassified